Analysis and Investigation of Religious Conflicts in Buyid Dynasty Era in Ray - Jahan Abad, Ali Fath Ghobadpour; Moftakhari, Hossein; Moghadam, Badrosadat Alizadeh; Jalali, Alireza (Journal of History Culture and Art Research, 2017)
In the fourth Hegira century, there were a lot of religious conflicts between madhab of Shia and Sunni as well as verbal discussion. The Buwaihids rulers were the governors of Iran and formed a government of Shia. Different Islamic religions were fighting with each other because of numerous governments of Buyid dynasty. There were numerous conflicts between Shia and Sunni in the most regions of Iran, especially in Ray. This paper investigates the religious conflicts in Buyid dynasty era in Ray City. So, it investigates the religious beliefs of Buyid dynasty rulers, scholars, and schools in Ray, then discusses about religious sectarians and verbal discussions on the basis of criticizing the refutation texts. Finally, he investigates the policy of Buwaihids rulers.